Approaches to modelling radioactive contaminations in forests – Overview and guidance. (November 2017) - Diener, A.; Hartmann, P.; Urso, L.; Vives i Batlle, J.; Gonze, M.A.; Calmon, P.; Steiner, M.
Abstract: Modelling the radionuclide cycle in forests is important in case of contamination due to acute or chronic releases to the atmosphere and from underground waste repositories. This article describes the most important aspects to consider in forest model development. It intends to give an overview of the modelling approaches available and to provide guidance on how to address the quantification of radionuclide transport in forests. Furthermore, the most important gaps in modelling the radionuclide cycle in forests are discussed and suggestions are presented to address the variability of forest sites. Highlights: This article describes the most important aspects to consider in forest model development. It gives an overview about forest modelling approaches and provides guidance for calculating the radionuclide fluxes. The most important gaps in modelling the radionuclide cycle in forests are discussed. It is intended for modellers, experimentalists, experts of national authorities and radiation protection advisers.